Formulasi dan Uji Antibakteri Masker Peel-Off Ekstrak Daun Gulma Siam (Chromolaena odorata L.) Terhadap Propionibacterium Acnes - Sari Wijayanti (Fakultas Farmasi Universitas Setia Budi, 2022)
Leaves of gulma siam (Choromolaena odorata L.) contain tannins, phenols, flavonoids, saponins, and steroids which are effective for killing acne-causing bacteria. Applied as anti-acne, the extract of gulma siam is formulated as a preparation of a peel-off gel mask. This research produces formulas of peel-off masks made from the extract of gulma siam leaves and perpetrates an antibacterial test on the peel-off masks against propionibacterium acnes. Four formulas of peel-off masks were made using different concentrations of the extract of gulma siam leaves. The concentrations were 3.25% (FI), 7.5% (FII), 15% (FIII), and 20% (FIV). The preparations of the peel-off masks were physically evaluated for organoleptic, spreadability, homogeneity, pH, viscosity, and dry time. A well diffusion method was implemented to test antibacterial potencies against propionibacterium acnes. The potency measurement was based on the resistance around wells in the form of a clear zone. Predicated on the evaluation results of the physical properties of gulma siam leave extracts during storage, organoleptically, the extracts were homogenous, had a pH of 4.5-6.5, and had a dry time of 15-21 minutes. Concerning spreadability, FIII and FIV lived up to the criteria. Meanwhile, for viscosity, all formulas of peel-off masks were unstable during storage. FI and FII presented weak and medium antibacterial activities, respectively. Moreover, FII and FIV showed strong ones. The ANOVA analysis showcased differences in antibacterial activities among the four formulas (p < 0.05). In conclusion, the extract of gulma siam leaves in the form of a peel-off mask preparation was a potential actibacterial ingredient for dealing with propionibacterium acnes.